Analysis of Heavy Metals in Coral Fish Species in Sea Natural Reserves of Krakatau Islands - Sri Muwarni (International Journal of Ecophysiology, 2019)
Krakatau Islands is an area of ​​Nature Reserve and Marine Nature Reserve which has volcanic activity, because of the existence of Gunung Anak Krakatau which is active every year. Volcanic ash erupted contains potentially hazardous chemicals in the form of heavy metals. Heavy metals that enter into waters at a certain level can cause pollution which endangers the lives of biota and disrupt other natural resources in marine ecosystems. This study aims to determine the concentration of heavy metals Pb, Ni, Cd, Cr, Fe, Mn, Zn, Co, and Ag in reef fish species in the Krakatau Islands. Fish sampling was carried out at three points, namely Anak Krakatau Island, Panjang Island and Rakata Island. The number of individuals obtained was 9 individuals consisting of 5 families, 5 genera and 7 species. Samples of Coral fish were analyzed using Inducible Coupled Plasma Optical Emission Spectrophotometry (ICP-OES - ThermoFishers Scientific). The Pb concentrations in P. vittatus, S. virgatus, S. schlegeli and A. xanthopper have exceeded the quality standard values ​​set by FAO. The highest concentration of Ni metal is found in P. vittatus and Cd in all reef fish species that have exceeded the quality standard. Excepted for S.virgatus, Co in all species is above the quality standard value of 0.1 mg/kg. Meanwhile, for all species obtained the concentrations of Cr, Mn, Fe and Zn did not exceed the standard quality values. The type of metal contained in Z. cornutus, the highest is Fe with a value of 14,427 mg/kg and the lowest is Co with a value of 0.099 mg /kg.